Exchanging experiences of technology partnership : Papers prepared for the Meeting of Experts on Technology Partnership for Capacity-building and Competitiveness, and recommendations, Helsinki, Finland, 10-12 April 1996. - United Nations Conference on Trade and Development; Finland; United Nations Conference on Trade and Development (New York : United Nations, 1996)
The publication presents papers prepared for an expert group meeting organized by the Finnish Ministry of Trade and Industry and UNICTAD's division for Science and Technology, in cooperation with the Programme for Development cooperation. The purpose was to exchange experiences on technology partnership for capacity building and competitivness
At head of title: United Nations Conference on Trade and Development, Geneva.
"Organized by the Ministry of Trade and Industry, Finland, and the UNCTAD secretariat (Division for Science and Technology), in cooperation with the Programme for Development Cooperation at the Helsinki School of Economics (PRODEC)."
"UNCTAD/DST/15."
"United Nations publication. Sales no. E.96.II.D8"--T.p. verso.
Includes bibliographical references.
opc 16/12/16
Keywords: Technology; Technology and state; Technology transfer